Research on the Artificial Intelligence Attribution Analysis and the Reasons for Decline of Physical Fitness of College Students in the Tropical Area under the Background of "Sunshine Sports" - Cui Zaichi; Jiang Yi; Hao Wenting; Huang Qian (MATEC Web of Conferences, 2019)
In 2010, the research team conducted a survey on the physical quality of 1600 college students in Hainan Province, and analyzed the changes in the physical quality of college students in Hainan from 2000 to 2010, and learned about the impact of sunshine sports on the physical quality of college students in Hainan Province. Based on this, a targeted intervention was proposed, which can provide reference for the sports workers and decision-makers in Hainan Province and improve the physical quality of students.